Cobalt(II), copper(II), and zinc(II) isostructural, pseudotetrahedral, racemic complexes of pyrrolo[2, 3-b]quinoxaline with bis(2-thienylmethyl)propylenediamine chain: Synthesis, crystal structure, spectroscopy. (1st February 2019) - Goszczycki, Piotr; Stadnicka, Katarzyna M.; Musielak, Bogdan; Ostrowska, Katarzyna
Graphical abstract: Cobalt, copper, and zinc ions form with pyrroloquinoxaline derivative the isostructural, pseudotetrahedral complexesΔ/Λ crystallizing in P 21 / c space group. The ligand in solid state has crystallization-induced planar chirality and adopts two conformations. Zinc complex2c is fluorescent both in solid state and in solution. Abstract: Cobalt(II), copper(II), and zinc(II) cations all have similar effective ionic radii so they form with ( E )-1-phenyl-3- N- [ N ′, N ′- bis (thiophen-2-ylmethyl)-3-aminopropyl]aminophenylmethylidene-1, 3-dihydro-2 H -pyrrolo[2, 3- b ]quinoxalin-2-one (1 ) isostructural, pseudotetrahedral complexes2a, 2b, and2c, respectively. Single crystal X-ray analysis of the synthesized complexes reveals that they are chiral (Λ-M-p S, p S ; Δ-M-p R, p R ) and crystalize as racemates in P 21 / c space group. There is axial chirality connected with tetrahedrally substituted metal center and crystallization induced planar chirality of two symmetry independent ligand molecules (different conformers). In solution only metal center chirality is maintained due to the conformational lability of the 3-[ N, N - bis (thien-2-ylmethyl)amino]propyl group. Chirality of zinc complex2c in solution was confirmed by the analysis of 1D and 2D NMR spectra. NMR data show diastereotopic protons of aliphatic chain and the restriction of phenyl ring rotation at C(30) carbon atom. Complex2c is fluorescent in solid state as well as in solution (fluorescence quantum yield in acetonitrile, ϕ = 0.1). The NMR titration at room temperature shows that the major product of zinc coordination is not2c but the complex with a tautomeric form of the ligand having proton located at N(4) nitrogen atom (enamine-imine tautomerism). UV–Vis data for2a, 2b, and2c both in solid and in solution are discussed.